Quasi-2D Lead–Tin Perovskite Memory Devices Fabricated by Blade Coating - Chen, Lijun; Xi, Jun; Tekelenburg, Eelco Kinsa; Tran, Karolina; Portale, Giuseppe; Brabec, Christoph J.; Loi, Maria Antonietta (Small Methods, 2023)
Two terminal passive devices are regarded as one of the promising candidates to solve the processor-memory bottleneck in the Von Neumann computing architectures. Many different materials are used to fabricate memory devices, which have the potential to act as synapses in future neuromorphic electronics. Metal halide perovskites are attractive for memory devices as they display high density of defects with a low migration barrier. However, to become promising for a future neuromorphic technology, attention should be paid on non-toxic materials and scalable deposition processes. Herein, it is reported for the first time the successful fabrication of resistive memory devices using quasi-2D tin–lead perovskite of composition (BA)2MA4(Pb0.5Sn0.5)5I16 by blade coating. The devices show typical memory characteristics with excellent endurance (2000 cycles), retention (105 s), and storage stability (3 months). Importantly, the memory devices successfully emulate synaptic behaviors such as spike-timing-dependent plasticity, paired-pulse facilitation, short-term potentiation, and long-term potentiation. A mix of slow (ionic) transport and fast (electronic) transport (charge trapping and de-trapping) is proven to be responsible for the observed resistive switching behavior.
CRIS-Team Scopus Importer:2023-06-30
Keywords: blade coating; charge trapping and de-trapping; ionic movements; quasi-2D Pb–Sn perovskite; synaptic plasticity